Strengthening Investigator Accountability through Cost Internalization in Indonesian Criminal Procedure Reform - Albariansyah, Hamonangan; Farhan, Ahmad Firjatullah (Kosmik Hukum, 2026)
Pre-trial procedure serves as a control mechanism over the authority of law enforcement officers, particularly in assessing the legality of coercive measures undertaken by investigators. In practice, courts have granted pre-trial applications in several cases and ordered compensation to be paid to applicants. However, a pre-trial decision does not automatically establish the state’s obligation to provide compensation; it must first be proven that the loss is real, measurable, and directly caused by unlawful actions. In general, such compensation is borne by the state through the national budget. Indonesian criminal procedural law does not explicitly regulate mechanisms for imposing compensation liability directly on investigators or other responsible state officials. Nonetheless, outside the criminal procedure framework, state financial law provides a mechanism for holding public officials accountable for losses resulting from negligence through administrative and financial liability systems. This study examines the potential application of cost internalization within the framework of economic and legal analysis to strengthen investigator accountability. By internalizing the costs arising from unlawful investigative actions, the burden of compensation may be shifted, at least partially, from the state to the responsible officials. The findings indicate that cost internalization represents an optimization of accountability, encouraging greater prudence and professionalism among investigators. Therefore, it is recommended that this concept be explicitly regulated in the Draft Criminal Procedure Code to enhance legal protection and institutional responsibility.